Improvements in hepatic steatosis, obesity, and insulin resistance in adults with nonalcoholic fatty liver disease after the primary obesity surgery endoluminal 2.0 procedure - AlKhatry, Maryam; Rapaka, Babusai; Maselli, Daniel B.; Abboud, Donna Maria; Brunaldi, Vitor O.; Mahmoud, Tala; Ghazi, Rabih; Abdul Razzak, Farah; Gala, Khushboo; Joudah, Imad; Housen, Fedaa; Al Qadi, Sana; Vargas, Eric J.; Storm, Andrew C.; Abu Dayyeh, Barham K. (Endoscopy, 2023)
Background The primary obesity surgery endoluminal 2.0 (POSE 2.0) procedure involves full-thickness gastric body plications to narrow the stomach using durable suture anchor pairs. We evaluated POSE 2.0 as a treatment strategy for nonalcoholic fatty liver disease (NAFLD) in patients with obesity.Methods Adults with obesity and NAFLD were prospectively allocated based on their preference to undergo POSE 2.0 with lifestyle modification or lifestyle modification alone (control). Primary end points were improvement in controlled attenuation parameter (CAP) and resolution of hepatic steatosis at 12 months. Secondary end points included %total body weight loss (%TBWL), change in serum measures of hepatic steatosis and insulin resistance, and procedure safety.Results 42 adult patients were included (20 in the POSE 2.0 arm and 22 in the control arm). At 12 months, POSE 2.0 significantly improved CAP, whereas lifestyle modification alone did not (P < 0.001 for POSE 2.0; P = 0.24 for control). Similarly, both resolution of steatosis and %TBWL were significantly higher with POSE 2.0 than with control at 12 months. Compared with controls, POSE 2.0 significantly improved liver enzymes, hepatic steatosis index, and aspartate aminotransferase to platelet ratio at 12 months. There were no serious adverse events.Conclusion POSE 2.0 was effective for NAFLD in patients with obesity, with good durability and safety profile.